An Improved Practical Measuring Technique for Wireless Cellular Signal Path Loss Forecast in the African Terrain (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Several studies on cellular signal path loss measurements at various locations under varying geographical and environmental circumstances in Africa have been conducted. Most of the techniques used, if not all, do not give consideration to the peculiar Africans’ road networks and building patterns, valleys, and hills that usually prevent the driving of motor cars within them when taking the signal strength measurements. The article presents an improved technique for wireless cellular signal strength measurement for better path loss prediction. The approach adopted for measurement is the regular grid outdoor foot technique. The technique was tested at various locations in the Ilorin metropolis and proved to be a better method of obtaining signal strength measurements. Although some of the signal strength values coincided with respect to distance when both methods were used, the drive test method overvalued the signal strength for study locations that were not in line of sight with the BTSs. These values range from 2 dBm to 8 dBm. If this technique is adopted, measurements will be taken in all vital locations that may not be accessible by means of a motor car drive test method, and more accurate values of the cellular signal strength will be obtained for better path loss prediction.
Keywords: BTS; Cellular Services; GSM; MU; Path Loss; RSSI